Comparison of the stellar populations of bulges and discs using the MaNGA survey - Lah, Philip; Scott, Nicholas; Barone, Tania M.; Robotham, A. S. G.; D’Eugenio, Francesco; Colless, Matthew; Casura, Sarah (Publications of the Astronomical Society of Australia, 2023)
We use the MaNGA integral field spectroscopic survey of low-redshift galaxies to compare the stellar populations of the bulge and disc components, identified from their Sérsic profiles, for various samples of galaxies. Bulge-dominated regions tend to be more metal-rich and have slightly older stellar ages than their associated disc-dominated regions. The metallicity difference is consistent with the deeper gravitational potential in bulges relative to discs, which allows bulges to retain more of the metals produced by stars. The age difference is due to star formation persisting longer in discs relative to bulges. Relative to galaxies with lower stellar masses, galaxies with higher stellar masses tend to have bulge-dominated regions that are more metal-rich and older (in light-weighted measurements) than their disc-dominated regions. This suggests high-mass galaxies quench from the inside out, while lower-mass galaxies quench across the whole galaxy simultaneously. Early-type galaxies tend to have bulge-dominated regions the same age as their disc-dominated regions, while late-type galaxies tend to have disc-dominated regions significantly younger than their bulge-dominated regions. Central galaxies tend to have a greater metallicity difference between their bulge-dominated regions and disc-dominated regions than satellite galaxies at similar stellar mass. This difference may be explained by central galaxies being subject to mergers or extended gas accretion bringing new, lower-metallicity gas to the disc, thereby reducing the average metallicity and age of the stars; quenching of satellite discs may also play a role.